2013
DOI: 10.1242/dev.083113
|View full text |Cite
|
Sign up to set email alerts
|

Lgr proteins in epithelial stem cell biology

Abstract: SummaryThe ultimate success of global efforts to exploit adult stem cells for regenerative medicine will depend heavily on the availability of robust, highly selective stem cell surface markers that facilitate the isolation of stem cells from human tissues. Any subsequent expansion or manipulation of isolated stem cells will also require an intimate knowledge of the mechanisms that regulate these cells, to ensure maintenance of their regenerative capacities and to minimize the risk of introducing undesirable g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
129
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 90 publications
(114 reference statements)
6
129
0
Order By: Relevance
“…Because canonical Wnt signaling is well-established as a key pathway supporting adult stem cells in a variety of contexts, one possibility was that the Wnt signaling we observed in the nail matrix might include activity in nail stem cells. Extensive work has shown that Lgr5 is a faithful marker of several epithelial adult stem cell populations (16) and has pinpointed Lgr5 as a key modulator of Wnt signaling in adult stem cell biology (23). We therefore set out to determine whether Lgr5 was expressed in the mouse digit tip, specifically in the nail epithelium.…”
Section: Lgr5 Expression Marks Mesenchymal Progenitors Local To Specimentioning
confidence: 99%
See 1 more Smart Citation
“…Because canonical Wnt signaling is well-established as a key pathway supporting adult stem cells in a variety of contexts, one possibility was that the Wnt signaling we observed in the nail matrix might include activity in nail stem cells. Extensive work has shown that Lgr5 is a faithful marker of several epithelial adult stem cell populations (16) and has pinpointed Lgr5 as a key modulator of Wnt signaling in adult stem cell biology (23). We therefore set out to determine whether Lgr5 was expressed in the mouse digit tip, specifically in the nail epithelium.…”
Section: Lgr5 Expression Marks Mesenchymal Progenitors Local To Specimentioning
confidence: 99%
“…Although Lgr4 is more broadly expressed in a wide range of tissues (14,15), Lgr5 and Lgr6 are tightly regulated and mark several adult stem cell populations throughout the body (16), including Lgr5 in the intestinal epithelium and hair follicle (17,18), as well as Lgr6 in the sweat glands and interfollicular epidermis (19). Canonical Wnt signaling has been shown to be necessary for appendage regeneration in many vertebrate epimorphic regenerative systems, including zebrafish fin, axolotl limb, and Xenopus tail (20)(21)(22).…”
mentioning
confidence: 99%
“…Lgr5 is also known to mark actively cycling stem cells in small intestine, colon, stomach, and hair follicle, as well as quiescent stem cells in liver, pancreas, and cochlea (8). Isolated Lgr5 + adult stem cells from multiple tissues are able to generate so-called organoid structures ex vivo (9)(10)(11).…”
mentioning
confidence: 99%
“…The requirement of CBL and CBL-B for the maintenance of MaSCs was independently confirmed by selectively inducing Cbl/ Cbl-b DKO in Lgr5 + MECs, which have recently been established as bi-potent MaSCs with MG-regenerating ability (Barker et al, 2007(Barker et al, , 2013. Tamoxifen-induced, MaSC-specific Cbl/Cbl-b DKO led to a rapid depletion of Lgr5 + cells (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Wnt ligands help propagate MaSCs in vitro (Kessenbrock et al, 2013;Wang et al, 2013;Zeng and Nusse, 2010) and partly mediate the hormonal regulation of MaSCs (Cai et al, 2014). The Wnt pathway target gene Lgr5, which marks epithelial stem cells in the intestine, skin and other tissues (Barker et al, 2007(Barker et al, , 2013, was recently shown to mark MaSCs (Plaks et al, 2013;Rios et al, 2014). Lgr5 + MaSCs can regenerate a MG upon transplantation (Plaks et al, 2013).…”
Section: Introductionmentioning
confidence: 99%